Brown fat and vascular heat dissipation: The new cautionary tail - Warner, Amy (Landes Bioscience, 2014)
Current efforts to treat obesity and associated disorders focus on the stimulation of energy expenditure by increasing thermogenesis, for instance through activating brown adipose tissue or more recently “beige” or “brite” fat, a relatively novel type of adipose tissue with putative thermogenic potential. In this commentary, we aim to provide an alternative perspective on the current trend of analyzing and manipulating thermogenesis, brought about by our recent publication, in which we investigated the unexpected hypermetabolic phenotype of an animal model with defective thyroid hormone receptor α1 signaling. These mice display elevated brown adipose tissue thermogenesis; surprisingly, however, their body temperature is lower, pointing to a defect in heat conservation. Using infrared thermography and wire myograph experiments, we revealed that the tail arteries of the mutant mice are less sensitive to contractile stimuli, which leads to insufficient peripheral vasoconstriction and heat loss over the tail surface. This heat loss in turn lowers body temperature and triggers the additional thermogenesis. Our findings add a new aspect to the role of thyroid hormone in thermoregulation, and encourage a more holistic view in future studies in the field of thermogenesis, including the often-overlooked heat dissipation and recordings of body temperature.